2021
DOI: 10.1038/s41598-021-00816-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-fire insect fauna explored by crown fermental traps in forests of the European Russia

Abstract: Wildfires considerably affect forest ecosystems. However, there is a lack of data on the post-fire status of insect communities in these ecosystems. This paper presents results of a study conducted in 2019 which considered the post-fire status of the insect fauna in a Protected Area, Mordovia State Nature Reserve (Republic of Mordovia, centre of European Russia), considered as regional hotspot of insect diversity in Mordovia. We sampled insects on intact (unburned, control) and fire-damaged (burnt in 2010) sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 94 publications
2
16
0
Order By: Relevance
“…Until recently, the fauna of the Drosophilidae of the Republic of Mordovia was totally unknown. The first paper with a short regional drosophilid faunistic list considered ecological questions of insect post-fire forest recovery [ 49 ]. This preliminary faunistic list includes 15 species in 6 genera of Drosophildae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, the fauna of the Drosophilidae of the Republic of Mordovia was totally unknown. The first paper with a short regional drosophilid faunistic list considered ecological questions of insect post-fire forest recovery [ 49 ]. This preliminary faunistic list includes 15 species in 6 genera of Drosophildae.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of seasonal changes on the abundance of Drosophilidae has been studied mainly in tropical and temperate climatic zones. Their abundance in tropical regions is affected by precipitation, and in regions with a temperate climate, temperature fluctuations are most affected [ 49 , 50 , 51 , 52 , 53 ]. Our studies have shown that Drosophilidae in central Russia have one peak in numbers, which begins at the end of September with a maximum in mid-October.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the glade, the largest number of P. marmorata was obtained at heights from 2 to 6 m, with a maximum number at a height of 4 m. The larvae of this species develop in the hollows of dead deciduous trees [71,72]. Imagos are anthophiles and are often found on flowering plants and shrubs [73,74]. Apparently, the anthophilicity of this species is due to the high-height preference in open habitats.…”
Section: Discussionmentioning
confidence: 99%
“…DISTRIBUTION. Widespread in Palearctic region (Bächli & Rocha Pité, 1984) and in the south of Russia (Gornostaev, 1997;Sidorenko, 2001), recently found in Mordovia (Ruchin et al, 2021;Gornostaev et al, 2022).…”
Section: Leucophenga Maculata (Dufour 1839)mentioning
confidence: 98%